PARTISIPASI POLITIK MASYARAKAT BORDER DI SAJINGAN BESAR DALAM PEMILIHAN UMUM DEWAN PERWAKILAN RAKYAT DAERAH - Elyta; Zulkarnaen (JURNAL BORNEO AKCAYA, 2016)
The community Borders the District of Sajingan not been enthusiastic in carry out elections of representatives Sambas Regency Area by 2014 as evidenced by the large number of difference in amount between the number of voters and the number of users voting rights in funneling his voice, even though the user voting rights in the total number of valid votes is very significant. The results showed that there are forms of political participation of border communities large and Sajingan two factors that lead to political participation that is an inhibitor of factor and the driving factor. Forms of political participation of the community in a big electoral exercise Sajingan Representatives Sambas County Area in 2014 including on election activities of the group, who only donate votes to tally election results. Restricting factors in political participation are (1) the bustle of daily activity most workers so prefer not to be involved in the implementation of the regional House of representatives election District of Sambas; 2) prohibition of the family at the request of participating families to give voting rights during the elections of representatives Sambas Regency Area. While the supporting factor of political participation is (1) a sense of wanting the public to be aware of the level of performance and commitment of the winner of the elections of the regional House of representatives elected later; 2) political consciousness of the voters who feel obliged in the launch of the implementation of the regional House of representatives election District of Sambas since it concerns the survival of the future.